Expressão de metaloproteinases e seus inbidores endógenos em câncer de pênis: estudos clínico-patológico e a relação com a infecção pelo HPV - BATISTA, Flávia Mendonça Lima (2022)
Penile cancer (PC) is one of the most common male tumors, with a high incidence in Brazil and worldwide, especially in the state of Maranhão. This cancer has a great capacity to invade locally and metastasize to regional lymph nodes, which is the most important prognostic factor, since metastasis to regional lymph nodes and the depth of invasion greatly reduce patient survival. This study is justified by the need to understand the factors that condition the invasive capacity of penile cancer, among them the regulation of MMPs 2 by TIMPs 2 and 3 and the relationship that this regulation has with the progression of this cancer, conditioning the invasive capacity of tumor cells. The overall objective was to analyze the expression of metalloproteinases (MMPs) and tissue inhibitors of metalloproteinases (TIMPs) in the development of HPV+ and HPV penile cancer through morphological and molecular studies. This is an epidemiological, analytical, qualitative, retrospective and sectional study of historical series of cases of penile epidermoid carcinomas, performed on 75 samples of penile tumors stored in the Biobanco de Tumores e DNA do Maranhão (BTMA). Sociodemographic data were obtained through a questionnaire, clinical and histopathological data were collected through medical record analysis. The genomic DNA of the samples was extracted and polymerase chain reaction PCR/Nested for HPV detection and then electrophoresis in agarose gel. Positive samples were submitted to genotyping by the Anyplex method for viral type identification. To analyze the expression of MMPs 2 and TIMPs 2 and 3 real time PCR was performed. It was observed that the mean age of patients at diagnosis was approximately 64 years. Most (64.76%) were from the interior of Maranhão and considered themselves to be brown (62.67%). It was also observed that 44.44% of patients were married, 30.56% had incomplete elementary school education, and 26.30% were illiterate. When asked about lifestyle habits, most patients (51.61%) said they never use condoms (63.51) that they smoke or have smoked during their lifetime. The majority (81.09%) also stated that they have been or still are alcoholics. It was also observed in this study that 49% of the samples were positive for HPV, with HPV 16 present in 36% and HPV 11 in 49% of the samples. The gene expression analyzed in this study showed an association between penile cancer, HPV infection and decreased expression of TIMP3 (p = 0,0360 entre tumores HPV+ e HPV-). With these results we can conclude that there is a relationship between some lifestyle habits of patients and penile cancer, as well as an important association with HPV infection. And also, that there is a relationship between HPV+ penile cancer and the downregulation of MMP expression, provided by the reduced expression of TIMP3.